Nation on right growth track due to wise financial management - New Sarawak, Tribune (New Sarawak Tribune, 2012)
SINTOK: Wise financial management, no heavy borrowing overseas and acting fast in the event of an economic crisis were the keys to putting the nation's economy on the right growth track.